CT Brain study to determine the site of predilection of intracranial lesions in HIV / AIDS patient with neurological symptoms and its association with toxoplasma and cryptoccal infections - Muhammad, Siti Jusna@Siti Sharifah (2006)
Objective: 1. To determine the distribution of intracranial lesions. 2. To find out the association between site of intracranial lesions with toxoplasma and cryptococcal infections. 3. To find out the association between CT findings with toxoplasma and cryptococcal infections. 4. To determine the association between CD4 count with toxoplasma and cryptococcal infections. Methods and Materials: Ethics committee approval and informed consent were obtained. This cross sectional study was carried out in Hospital USM, Kubang Kerian and Hospital Raja Perempuan Zainab II (HRPZ II) for 12 months from January 2005 until December 2005. Plain and contrast cranial CT scan were performed on a total of 56 HIV patients with neurological signs and symptoms. Results: There were 7/56 (12.5 %) middle stage and 49/56 (87.5%) late stage patients. Majority of patient presented with non-focal symptoms 52/56 (92.9%) in which headache was the most frequent complaint 17/52 (32.7%). Patient with toxoplasmosis and cryptococcosis constituted 70.7% (29/41) and 23.3% (10/43) oftotal subject investigated. CT scans were normal in 13 (23.2%) and abnormal in 43 (76.85) cases. Majority of the lesions were multiple 24/38 (63.2%). In general, lesions were mostly found in supratentorial region within the parietal (73.7%) followed by occipital (55.3%), frontal (47.4%) and temporal(36.8%) lobes. Basal ganglia regton was affected in 52.6% of cases. Patients with Toxoplasmosis had lesions at frontal lobe in 31%, parietal lobe in 58.6%, occipital lobe in 34.5%, temporal lobe in 20.7% lobe and 34.5% at basal ganglia area. In patients with cryptococcosis, lesions were found 40% at parietal lobe, 30% at occipital lobe, I 0% at temporal lobe and 10% at basal ganglia area. No lesion was found at frontal lobe in those patients with cryptococcosis in this study. No association was detected between CD4 counts or CT findings with etiology of the lesion (Toxoplasma and Cryptococcus) and between etiologies of lesion with site of intracranial lesions in this study Conclusion: We conclude that in general, parietal lobe is commonly involved in both opportunistic infections. No association was detected between CD4 counts or CT findings with etiologies of the lesion and between etiologies of lesion with site of intracranial lesions in this study. Toxoplasmosis however was a major opportunistic organism giving rise to various CNS manifestations in our HIV -infected patients with potential significant contribution of tuberculosis and cryptococcosis. Frontal lobe, temporal lobe and basal ganglia however, are more commonly involved in HIV patients with toxoplasmosis than in HIV patients with cryptococcosis.